The Practice of Texts Education and Healing in South India (Edition 1) - Cerulli, Anthony (University of California Press, 2022)
The Practice of Texts examines the uses of the Sanskrit medical classics in two educational institutions of India's classical life science, Ayurveda: the college and the gurukula. In this interdisciplinary study, Anthony Cerulli probes late- and postcolonial reforms in ayurvedic education, the development of the ayurvedic college, and the impacts of the college curriculum on ways that ayurvedic physicians understand and use the Sanskrit classics in their professional work today. His fieldwork in south India illuminates the nature of philology and ritual in the ayurvedic gurukula and showcases how knowledge is exchanged among students, teachers, and patients. The result, Cerulli shows, is that the Sanskrit classics are presented and applied differently in the college and gurukula, producing a variety of relationships with these texts among practitioners. By interrogating the politics surrounding the place of the Sanskrit classics in ayurvedic curricula, this book reveals a spectrum of views about the history and tradition of Ayurveda in modern India.